2021
DOI: 10.1097/md.0000000000024868
|View full text |Cite
|
Sign up to set email alerts
|

The Use of hx-index to compare research achievements for ophthalmology authors in Mainland China, Hong Kong, and Taiwan since 2010

Abstract: Background: Ophthalmology authors in mainland China, Hong Kong, or Taiwan were interested in knowing their individual research achievements (IRAs). This study was to evaluate the most cited authors, institutes, and regions in the mainland, Hong Kong, and Taiwan in the field of ophthalmology in the recent 10 years using the hx-index and to display the result with visual representations. Methods: Using the PubMed search engine to download data, we conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 27 publications
(22 reference statements)
0
28
0
Order By: Relevance
“…[8] For assessment of research productivity and impact, [5] some fractional counting by the first or corresponding author was applied (e.g., author weighted scheme). [6,20,21] First-author articles have been used as a measure of authors' performance in general surgery journals, [22] anesthetic journals, [23] ophthalmology journals, [24] rehabilitation journals, [25] biomedical research journals, [26] urology journals, [27] and orthopedic surgery journals. [28] The number of coauthored articles by Chinese authors was also noted as a reflection of their research responsibility.…”
Section: Scientific Productivity Assessed Using the Y-indexmentioning
confidence: 99%
“…[8] For assessment of research productivity and impact, [5] some fractional counting by the first or corresponding author was applied (e.g., author weighted scheme). [6,20,21] First-author articles have been used as a measure of authors' performance in general surgery journals, [22] anesthetic journals, [23] ophthalmology journals, [24] rehabilitation journals, [25] biomedical research journals, [26] urology journals, [27] and orthopedic surgery journals. [28] The number of coauthored articles by Chinese authors was also noted as a reflection of their research responsibility.…”
Section: Scientific Productivity Assessed Using the Y-indexmentioning
confidence: 99%
“…There are four factors that contribute to the CJAL score: subject category, journal impact factor, authorship in positions on the article byline, and article citations. The evaluation of individual RAs has traditionally been based on bibliometric metrics (e.g., h-index, [ 60 ] g-index, [ 61 ] x-index, [ 62 ] hx-index, [ 63 ] author impact factor, [ 64 ] Y-index, [ 42 ] and hT-index [ 65 , 66 ] ). These metrics have a number of disadvantages, such as assuming that all coauthors contributed equally to the article, regardless of the type of document or journal impact factor.…”
Section: Discussionmentioning
confidence: 99%
“…[33] However, the only practical solution is to split them equally (i.e., to assign each coauthor 1/n of the authorities, where n is the total number of authors), as shown in equation 1. Although the author-weight scheme was proposed to share article credits based on the order of the authors, [8,11,17,34,35] it is straightforward to substitute wi for 1/ a i in equation 1. The author’s order is not considered in this study.…”
Section: Discussionmentioning
confidence: 99%